2021
DOI: 10.3389/fdgth.2021.576514
|View full text |Cite
|
Sign up to set email alerts
|

“You Are on the Right Track With the App:” Qualitative Analysis of Mobile Phone Use and User Feedback Regarding Mobile Phone Sexual Risk Assessments for HIV Prevention Research

Abstract: Background: Accurate self-report of sexual behavior assists in identifying potential HIV exposure in HIV prevention trials. Brief mobile phone assessments, completed daily or after sexual activity, can improve the validity and reliability of self-reported sexual behavior and allow for remote survey completion outside of the clinic setting. We conducted a qualitative study to better understand participants mobile phone use and to explore their perspectives on how to improve an existing mobile application-based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 32 publications
(150 reference statements)
1
6
0
Order By: Relevance
“…Mobile health technologies for HIV prevention have been used to increase awareness of available sexual health services, ensure privacy and to decrease awkwardness in HIV self-risk assessments with a health provider present [ 57 ]. Some mhealth platforms have applied a PrEP Information-Motivation-Behavior-skills (IBM) model tailored to key populations to promote PrEP adherence or reduction in risk behaviors [ 57 59 ].…”
Section: Mobile Apps Telemedicine and Home-based Hiv Preventionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mobile health technologies for HIV prevention have been used to increase awareness of available sexual health services, ensure privacy and to decrease awkwardness in HIV self-risk assessments with a health provider present [ 57 ]. Some mhealth platforms have applied a PrEP Information-Motivation-Behavior-skills (IBM) model tailored to key populations to promote PrEP adherence or reduction in risk behaviors [ 57 59 ].…”
Section: Mobile Apps Telemedicine and Home-based Hiv Preventionmentioning
confidence: 99%
“…Mobile health technologies for HIV prevention have been used to increase awareness of available sexual health services, ensure privacy and to decrease awkwardness in HIV self-risk assessments with a health provider present [ 57 ]. Some mhealth platforms have applied a PrEP Information-Motivation-Behavior-skills (IBM) model tailored to key populations to promote PrEP adherence or reduction in risk behaviors [ 57 59 ]. mHealth applications use videos, games, animation, or chatbots to deliver personalized care to users in the form of self-risk evaluation, pill-taking reminders, addressing peer and social norms, considering disclosure, or scheduling follow-up health appointments [ 60 ].…”
Section: Mobile Apps Telemedicine and Home-based Hiv Preventionmentioning
confidence: 99%
“…Therefore, we planned to provide entry level android smartphones to 20% of participants enrolled in the study. Previous qualitative research on mobile phone-based data collection conducted among youth in Soweto indicated a preference for short surveys that were easy to answer, with mobile phone data provided to participants to access the applications for survey completion, followed by an airtime incentive, a voucher that could be redeemed immediately for mobile phone airtime, after survey submission [13][14][15]. Additionally, reminder messages were recommended for repeated EMA mobile phone based surveys [14].…”
Section: Initial Literature Reviewmentioning
confidence: 99%
“…In the US, a recent literature review on EMA in HIV research identified EMA methods using smartphone apps for HIV primary prevention, HIV treatment adherence, and substance use among young adults and adult populations [12]. Notably, previous South African research utilising daily mobile phone EMA measures was conducted among young women 18-24 years to assess HIV risk and showed more accurate reporting via the mobile phone when compared to the in-clinic survey measure [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…This article describes the formative qualitative research phase that was undertaken to contextualise and inform the subsequent co-design process [18] in one of the research sites, the urban township setting of Soweto in Johannesburg Metropolitan Municipality. Previous qualitative research on digital health has been limited in settings like Soweto [19,20]. A better understanding of the socio-technical challenges and opportunities that digital health technologies afford is needed in the context of maternal and child health in Soweto, especially with regards to the COVID-19 pandemic and resulting shifts to digital technologies [9,21].…”
Section: Introductionmentioning
confidence: 99%